MENGKAJI RELASI AGAMA DAN MOTIVASI EPISTEMIK - Istiqomah Istiqomah (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2022)
Religion functions adaptively and helps provide a sense of coherence, control, and reduces ambiguity. Some Muslims are described as believing in and understanding Islamic teachings as a comprehensive (total) guide in all aspects of life including political and state life. The research aims to determine the relationship between Islamic totalism and epistemic motivation (need for cognitive closure). Through a non-experimental survey of 376 Muslim students in Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek) with measuring instruments of Islamic totalism and need for cognitive closure. The results of the study show that there is a significant positive correlation between Islamic totalism and empirical motivation. These results illustrate that Muslims with a high need for cognitive closure have a need to reduce uncertainty, perfect Islamic teachings are considered as epistemic authorities that can provide certainty and help navigate a social world that threatens to be ambiguous and complex